Kerjasama Australia dan Indonesia dalam Upaya Pengembangan Sektor Pendidikan Di Australia Melalui Organisasi ACICIS (Australian Consortium For In-Country Indonesian Studies) - Ismiyatun Ismiyatun; Diah Ariyanti (LP2M, 2019)
ABSTRACT This study analyzes the collaboration between Australia and Indonesia in the development of the education sector in Australia through the ACICIS (Australian Consortium for In-Country Indonesian Studies) organization which was established in 1994. ACICIS is a consortium of non-profit universities that develops and coordinates various study options quality in Indonesia for Australian, non-Australian and individual students. The reason Australia and Indonesia collaborate in the education sector is to improve the quality and quality of education in both countries, at the university level. In this journal, we discuss how cooperation between Australia and Indonesia in the education sector through the ACICIS organization. To find out the system of cooperation between the two parties, in carrying out this collaboration, researchers used an approach to the theory of international cooperation. Keywords: ACICIS (Australian Consortium for In-Country Indonesian Studies), international cooperation, education.